2019
DOI: 10.1186/s12877-019-1373-y
|View full text |Cite
|
Sign up to set email alerts
|

How older patients prioritise their multiple health problems: a qualitative study

Abstract: BackgroundPatients with multimorbidity often receive diverse treatments; they are subjected to polypharmacy and to a high treatment burden. Hence it is advocated that doctors set individual health and treatment priorities with their patients. In order to apply such a concept, doctors will need a good understanding of what causes patients to prioritise some of their problems over others. This qualitative study explores what underlying reasons patients have when they appraise their health problems as more or les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
2
9
0
2
Order By: Relevance
“…Several studies [ 15 , 16 , 18 , 22 ], have reported that patients prioritise health conditions based on their functional impact, and this study reports similar findings. Analysis of specific capacity domains showed that pain and mental health conditions (as well as diabetic foot ulcers) had the greatest impact on capacity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies [ 15 , 16 , 18 , 22 ], have reported that patients prioritise health conditions based on their functional impact, and this study reports similar findings. Analysis of specific capacity domains showed that pain and mental health conditions (as well as diabetic foot ulcers) had the greatest impact on capacity.…”
Section: Discussionsupporting
confidence: 81%
“…In clinical practice, this has led to each condition being managed as a separate entity [ 10 ], with precedence given to conditions with a higher risk of future adverse outcomes such as diabetes or cardiovascular disease [ 13 , 14 ]. Interviews with patients suggest that they approach multimorbidity differently, placing greater importance on symptomatic conditions affecting their quality of life [ 15 19 ]. This preference has implications for health outcomes, with conditions that may have low symptom burden but high future risk being deprioritised or ignored by patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, o que ocorre no cotidiano dos serviços é que pacientes com multimorbidade, geralmente, recebem tratamentos diversos; estão sujeitos à polifarmácia e a uma alta carga de tratamento. Muitas vezes, ainda, a decisão pelas prioridades individuais de saúde e tratamento conta muito pouco com a percepção do próprio idoso, estando, com frequência, ligada à gravidade das doenças e, principalmente, às restrições provocadas nas atividades diárias, autonomia e inclusão social (JUNIUS-WALKER et al, 2019). Supõe-se, portanto, que perguntar aos pacientes com multimorbidade que problemas de saúde são importantes pode orientar a equipe de saúde para as prioridades de tratamento e problemas de saúde que necessitam de empoderamento.…”
Section: Discussionunclassified
“…Having a shared understanding of the uncertainty of the patient’s condition could enable the family to adjust expectations of level of recovery and support the patient’s adaptation to change in function as well as continuity of care. For older people, psychological adjustment to conditions may be a lower priority than problems that hinder their independence [ 38 ]. Understanding the patient’s priorities for care is key to understand how older patients prioritise their multiple health conditions.…”
Section: Discussionmentioning
confidence: 99%